FORMULATION AND EVALUATION OF MEDICATED LOZENGES FOR SORE THROAT - CHANDA, RUPALI; NALLAGUNTLA, LAVANYA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The objective of the present work was to formulate and evaluate lozenges for a sore throat using Loratadine. Loratadine is a long-acting peripheral H1-receptor antagonist which is mainly used as an antihistamine. Loratadine lozenges were prepared to prevent the itching and inflammation in sore throat. Methods: Solid dispersion of Loratadine was prepared using β-cyclodextrin in the ratios of 1:1, 1:2, and 1:3 to enhance the solubility of Loratadine. The prepared solid dispersion of Loratadine was analyzed for solubility enhancement. Loratadine lozenges were then formulated with mannitol, sucrose, acacia, xanthan gum, liquid glucose by heat, and congealing technique. The prepared lozenges were evaluated for drug-excipient incompatibility study, diameter, thickness, weight variation, hardness, friability, in vitro release study, and drug content. Results: The results of the Fourier transform infrared study showed that there was no interaction between the selected drug and excipients. In vitro drug release study of Loratadine lozenges were performed in pH 6.8 phosphate buffer, wherein >90% of the drug was released within 30 min for all the formulations. The lozenges were optimized based on in vitro release data. Formulation F7 of Loratadine lozenges exhibited 99.1% release in 30 min. Stability studies revealed that the formulation was stable. Conclusion: From the present work, it was concluded that the Loratadine lozenges can be considered as a suitable delivery system for the treatment of sore throat.